Humanizing NOD/SCID/IL-2Rγnull (NSG) mice using busulfan and retro-orbital injection of umbilical cord blood-derived CD34(+) cells - Kang, Young Kyung (Blood Res, 2016)
BACKGROUND: Humanized mouse models are still under development, and various protocols exist to improve human cell engraftment and function. METHODS: Fourteen NOD/SCID/IL-2Rγnull (NSG) mice (4‒5 wk old) were conditioned with busulfan and injected with human umbilical cord blood (hUCB)-derived CD34(+) hematopoietic stem cells (HSC) via retro-orbital sinuses. The bone marrow (BM), spleen, and peripheral blood (PB) were analyzed 8 and 12 weeks after HSC transplantation. RESULTS: Most of the NSG mice tolerated the regimen well. The percentage of hCD45(+) and CD19(+) cells rose significantly in a time-dependent manner. The median percentage of hCD45(+)cells in the BM was 55.5% at week 8, and 67.2% at week 12. The median percentage of hCD45(+) cells in the spleen at weeks 8 and 12 was 42% and 51%, respectively. The median percentage of hCD19(+) cells in BM at weeks 8 and 12 was 21.5% and 39%, respectively (P=0.04). Similarly, the median percentage of hCD19(+) cells in the spleen at weeks 8 and 12 was 10% and 24%, respectively (P=0.04). The percentage of hCD19(+) B cells in PB was 23% at week 12. At week 8, hCD3(+) T cells were barely detectable, while hCD7(+) was detected in the BM and spleen. The percentage of hCD3(+) T cells was 2‒3% at week 12 in the BM, spleen, and PB of humanized NSG mice. CONCLUSION: We adopted a simplified protocol for establishing humanized NSG mice. We observed a higher engraftment rate of human CD45(+) cells than earlier studies without any significant toxicity. And human CD45(+) cell engraftment at week 8 was comparable to that of week 12.